Emergence of G12P[6] rotavirus strains among hospitalised children with acute gastroenteritis in Belém, Northern Brazil, following introduction of a rotavirus vaccine - Guerra, Sylvia de Fátima dos Santos (2019)
Species A rotavirus still remains a major cause of acute gastroenteritis in infants and young children. Globally, six genotypes (G1P[8], G2P[4], G3P[8], G4P[8], G9P[8] and G12P[8]) account for >90% of circulating strains; however, genotype G12 in combination with P[6] or P[9] has been detected at increasing rates. We sought to broaden our knowledge about the rotavirus strains circulating during the early post-vaccine-introduction period. Stool samples were obtained from children hospitalised for acute gastroenteritis in Belém, Northern Brazil, from May 2008 to May 2011 and examined by reverse transcription polymerase chain reaction and nucleotide sequencing. A total of 122 out of the original 1076 rotavirus strains were judged to be non-typeable in the first analysis and were therefore re-examined. G2P[4] was the most prevalent genotype (58.0%), followed by G1P[8] (16.9%), and G12P[6] (7.5%). G12P[6] strains were identified at similar rates during the first (2.5%) and second (3.9%) years, and the rate jumped to 15.6% in the third year. Analysis of VP7 sequences of the G12P[6] strains showed that they belonged to lineage III. In addition, co-circulating G12P[6] strains displaying long and short RNA patterns were found to belong to the Wa-like and DS-1-like constellation, respectively. Additional unusual circulating strains G12P[9] and G3P[9] were also identified. This hospital-based study showed a high prevalence of G12P[6] strains in the third year of surveillance. Our results highlight the need for continuous longitudinal monitoring of circulating rotavirus strains after introduction of rotavirus vaccines in Brazil and elsewhere.